Strategi Pemasaran Usaha Ekspor Briket Arang Tempurung Kelapa pada PT. Taiba Cococha Indonesia - Effendi, Al-Azhar Fitrah; Harimurti, Cundo (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
This research was conducted to determine the marketing strategy of export businesses coconut shell charcoal briquettes at PT. Taiba Cococha Indonesia and obstacles and efforts made. This research uses the method qualitative research of a descriptive nature. Data collection from This research is by interview and observation. Data sources on This study used data collection techniques in this study the author made a direct visit to PT. Taiba Cococha Indonesia to conduct interviews. Marketing strategy of PT. Taiba Cococha Indonesia's doing so is by making various innovations by maximizing customer service and improving product quality coconut shell charcoal briquettes. Other strategies that conducted PT. Taiba Cococha Indonesia is by improving marketing through social media to reach a wider market.